PENGGUNAAN METODE “RESEP MATEMATIKA” PADA MATERI OPERASI HITUNG BILANGAN PECAHAN - Indah Suciati (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2022)
The fraction count operation is one of the problems often faced by students on the topic of fraction numbers. Even though the material is important and is often applied, there are still many students who make mistakes. The errors most often experienced by students are procedural errors. To solve this problem, a solution is given to the application of the